High-salt diets provoke phosphorus absorption from the small intestine in mice - Mingxin Yang; Huaizhou You; Li Ni; Jianping Mao; Jing Chen (Clinical and Experimental Hypertension)
Background Recent studies indicate that tenapanor, an inhibitor of sodium/proton exchanger-3 (NHE3), diminishes intestinal phosphorus (Pi) absorption. Given NHE3’s pivotal role in sodium (Na+) metabolism, there is a suspected functional link between Na+ and Pi metabolism. High-salt diets (HSD) have been demonstrated to disrupt calcium (Ca2+) metabolism. Since Ca2+ and Pi share analogous metabolic pathways, it is yet to be determined whether HSD also impacts Pi metabolism.Methods Male C57 mice were randomly assigned to three groups: a standard diet group, HSD groups for 1 week (HSD-1w) and 4 weeks (HSD-4w). Throughout the study, dietary intake and water consumption were monitored using metabolic cages, and urine and feces were collected. Blood pressure was measured using a noninvasive tail vein sphygmomanometer. Upon completion of the intervention, mice were euthanized under anesthesia for blood collection, and intestinal and renal tissues were harvested for molecular analysis.Results Although plasma Pi levels were comparable between HSD groups and the control group, HSD groups exhibited increased urinary Pi excretion and decreased fecal Pi excretion. The HSD-4w group displayed elevated parathyroid hormone levels, reduced fibroblast growth factor 23 levels, and higher renal Cyp27b1 mRNA expression. The expression of sodium-dependent phosphate transporter 2b (Npt2b) and NHE3 was elevated in the intestine of HSD mice.Conclusion HSD disrupts Pi metabolism by enhancing urinary Pi excretion and altering hormonal levels. The decrease in fecal Pi excretion, coupled with the upregulation of intestinal Pi transporter expression, suggests that HSD promotes intestinal Pi absorption in mice.